1994
DOI: 10.1128/aac.38.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an antacid containing magnesium and aluminum on absorption, metabolism, and mechanism of renal elimination of pefloxacin in humans

Abstract: The effects of an antacid containing magnesium and aluminum hydroxide on the pharmacokinetics of pefloxacin in 10 healthy volunteers were investigated. In a randomized crossover design, each subject received an oral dose of 400 mg of pefloxacin either with or without multiple doses of the antacid. The concentrations of pefloxacin and its metabolites in plasma and urine were determined by high-performance liquid chromatography assays. We found that coadministration of magnesium and aluminum hydroxide caused a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Physical adsorption to aluminum hydroxide gel has been proposed as a second mechanism, which may affect hydrophilic fluoroquinolone derivatives such as ciprofloxacin, norfloxacin, and enoxacin in particular, while lipophilic compounds are less affected [43]. The interaction is further facilitated by the lack of a substituent at the 5-position of ciprofloxacin [44].…”
Section: Discussionmentioning
confidence: 98%
“…Physical adsorption to aluminum hydroxide gel has been proposed as a second mechanism, which may affect hydrophilic fluoroquinolone derivatives such as ciprofloxacin, norfloxacin, and enoxacin in particular, while lipophilic compounds are less affected [43]. The interaction is further facilitated by the lack of a substituent at the 5-position of ciprofloxacin [44].…”
Section: Discussionmentioning
confidence: 98%
“…Plasma samples were analyzed for caffeine, 18 unchanged pefloxacin, 19 and unchanged enoxacin 20 by reversed‐phase HPLC assays. Concentrations of metabolites of caffeine or of quinolones were not determined in the vivo studies.…”
Section: Methodsmentioning
confidence: 99%
“…This is because enoxacin ligand interacted with the metal ions possibly leading to the formation of drug metal chelates. 13 It was further observed that the ability of enoxacin to interact with metal ion was pH dependent and was greater in extreme pH conditions i.e. pH 1.5 and pH 9.…”
Section: Spectrophotometric Analysismentioning
confidence: 97%